Ecotoxicological Assessment of Virgin Plastic Pellet Leachates in Freshwater Matrices - Schiavo, S.; Oliviero, M.; Romano, V.; Dumontet, S.; Manzo, S. (Journal of Environmental Accounting and Management, 2026)
The environmental contamination caused by the widespread diffusion of plastic material all over the world is a topic of high concern. Virgin plastic pellets of different polymers are often used in particle toxicity studies as reference materials. In this study we exposed organisms of different trophic levels, spanning form prokaryotes to eukaryotes, to leachate of polypropylene (PP) and polyethylene (PE), and polystyrene (PS) pellets in acute and chronic ecotoxicological tests. A toxicity test battery integrated index (TBI) was used to rank the relative toxicity of studied polymers and to define their possible ecotoxicological risk in freshwater environment. Daphnia magna showed the highest susceptibility in the chronic exposure tests (around 50% of effect) while Aliivibrio fischeri (around 25 % of effect) in the acute one. No relevant toxic effects were observed on Sorghum saccharatum, Lepidium sativum and Sinapis alba seeds, while significant toxicity for Vicia faba along 21 days of exposure was reported. TBI allowed us to rank the toxicity risk associated to the studied materials as follows: PP>PS>PE. PP toxicity could be related to the presence of solvents (methanol, oil, cyclohexane) employed for its production, whereas PS toxicity was probably due to the depolymerization, occurring in water, followed by styrene release, while the mild toxic effects of PE and its temporary bio stimulation could be attributable to the thermoregulatory additives present in the polyethylene resins. Our results highlighted that also the virgin plastic pellets could be responsible of toxic effects that should not be neglected.